Adenocarcinoma of the parotid salivary gland in a cow - Salgado, Breno S. [UNESP]; Monteiro, Lidianne N. [UNESP]; Grandi, Fabrizio [UNESP]; Nonogaki, Suely; Rocha, Rafael M.; Rocha, Noeme Sousa [UNESP] (Wiley-Blackwell, 2012)
A 6-year-old Girolando dairy cow was presented for evaluation of a large subcutaneous facial mass. Fine-needle aspirates of the mass contained many neoplastic cells with high nuclear:cytoplasmic ratios arranged in sheets and loosely cohesive clusters with streaming erythrocytes and neutrophils in the background. Neoplastic cells were 1325 mu m in diameter and were round to cuboidal with variably distinct borders. Based on the signalment, anatomic location, and cytologic findings, differential diagnoses included salivary adenocarcinoma, squamous cell carcinoma, and mucoepidermoid carcinoma. The cow was euthanized and a necropsy was performed. The primary neoplasm arose from the left parotid salivary gland and meastatic tumor was found in the regional lymph nodes and lung. Histologically, the tumor was composed of anastomosing and irregular solid islets surrounded by scant stroma. Cells were negative for periodic acid-Schiff (PAS), PAS-diastase, and Alcian blue pH 2.5 stains, used to detect mucin. on immunohistochemical analysis, neoplastic luminal salivary gland cells expressed cytokeratin, but not S100, a-smooth muscle actin, or vimentin. Peripheral cells of neoplastic islets were immunoreactive for p63. The final diagnosis was nonsecretory adenocarcinoma of the parotid salivary gland.
Keywords: Cattle; cytology; immunohistochemistry; mucoepidermoid carcinoma; p63